2011
DOI: 10.1007/s11746-011-1934-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Limonene on the Crystallization of Cocoa Butter

Abstract: The formulation of reduced fat chocolate has been of interest to the confectionery industry for a considerable time. It presents a challenge, as fat reduction strategies are often accompanied by poor quality of the formulated product due to an increased viscosity of the molten chocolate. This causes difficulties during processing and poor sensory properties of the final product. The addition of limonene to chocolates leads to fat reduced chocolates that are less hard and have a lower melt viscosity. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
4
25
0
7
Order By: Relevance
“…Similar effect has been shown at 17°C by Rigolle et al [27]. Limonene enhances the transformation to more stable cocoa butter polymorphic form β V [26,27]. The latter is the desired form for chocolate manufacture as the melting temperature of this form is high enough (34-36°C) to maintain the chocolates in solid form at room temperature and low enough for the chocolate to melt in the mouth [28].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Similar effect has been shown at 17°C by Rigolle et al [27]. Limonene enhances the transformation to more stable cocoa butter polymorphic form β V [26,27]. The latter is the desired form for chocolate manufacture as the melting temperature of this form is high enough (34-36°C) to maintain the chocolates in solid form at room temperature and low enough for the chocolate to melt in the mouth [28].…”
Section: Resultssupporting
confidence: 69%
“…[24,25]. Ray et al [26] observed that with the addition of limonene to cocoa butter, the isothermal crystallization of chocolate starts earlier at temperatures from 17 to 20°C. Similar effect has been shown at 17°C by Rigolle et al [27].…”
Section: Resultsmentioning
confidence: 99%
“…Soy lecithin and sorbitan esters are primarily used as emulsifiers and they are known to act as crystallization modifiers . Recent studies have demonstrated the use of d ‐limonene as a potential additive in CB crystallization processes . d ‐Limonene is a monoterpene and is a constituent of citric fruit essential oils.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its citric aroma, d ‐limonene has been widely used as an aromatizing agent in beverages, chewing gum, perfumes, and chocolate, conferring an orange aroma . According to Ray et al , the addition of 5% d ‐limonene to CB promotes the complete polymorphic transition from the βV to βVI form when storage during 21–28 days at 20°C. Do et al stated that d ‐limonene may be located between the fatty acids chains in the TAG and influences the properties of fat crystal network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation